Advanced prostate cancer – optimising and integrating care. Issue 1 (28th January 2013) - Payne, Heather A.; Farnham, Chris; Kirby, Mike; Troup, Janis
Abstract This report summarises discussions led by specialists in secondary, primary and palliative care during a series of four regional meetings organised by the British Uro‐oncology Group in partnership with Macmillan. The aim of these meetings was to debate appropriate pathways of care for patients with advanced disease, focusing on sequencing of therapy and palliative care. They also provided a forum to increase awareness and understanding across professional disciplines of NHS reforms and commissioning processes in the field of prostate cancer. Copyright © 2013 John Wiley & Sons